POSSIBILITIES OF HEPATITIS C ANTIVIRAL TREATMENT IN LIVER TRANSPLANT RECIPIENTS - V. E. Syutkin; O. I. Andreytzeva; A. V. Chzhao (Вестник трансплантологии и искусственных органов)
The results of 21 courses of antiviral therapy (AT) in 18 pts with HCV infection after cadaveric liver transplan- tation have been analyzed. (One recipient received AT twice due to noncompliance and two patients re-started AT PEG-IFN monotherapy). AT included PEG–IFN alpha-2a (180 mcg/w) in 18 cases or PEG-IFN alpha-2b (1,5 mcg/kg/w) in 3 cases combined with RBV (9,9 (3,3) mg/kg/day). Since 2008 epoetin-alfa (30,000 U/w) and filgrastim (300 mcg/w) were added to correct cytopenias for all treatment duration. Sustained virologic response was achieved in 25% cases (ITT) or in 40% cases (completed 80/80/80 rule per protocol). Rapid virologic res- ponse occurred only in 2 patients with non-1 genotype HCV with respectively low viral load, and complete early virologic response (EVR) – in 10 (56%) of 18 patients. Complete EVR occurred in all non-1 genotype pts, but only in 5/13 pts with HCV genotype 1 (p = 0,036). Four pts achieved negative serum HCV RNA post 12 week of AT. The early viral dynamic is slower in AT of recurrent HCV infection in liver transplant recipients than in non-transplanted patients. Growth factors can safely and effectively be used in complex treatment of hepatitis C after liver transplantation.